Apiariusz z Sicca Veneria i odwoływanie się do Ojców na synodach Afryki Łacińskiej (IV-VI w.) - Degórski, Bazyli (Vox Patrum, 2023)
The series of texts from the synods of the African Latin Church that speak of appealing to the Fathers contain strong arguments that irrefutably testify to the fact that the synodal fathers were convinced that it was always necessary to rely on the authority of the Fathers who lived earlier and to refer to the indisputable Tradition. We also learn from them that the expression “fathers” (or rare analogous forms such as, for example, “brothers” – ἀδελφοί, fratres) is synonymous with “Tradition”, since it is closely associated with the authority of the Councils, in particular the First Council of Nicaea, whose essential dogmatic significance is unparalleled in the history of the Church. The consequence of recognising the First Council of Nicaea as indisputable Tradition is to give the statements of the Fathers a normative character binding even on the Roman Church. A reading of the documents of the African synods reveals an increasing clarification of the determinants of Tradition: apostolic origin, antiquity, universal acceptance. But it is above all the recognition of the action of the Holy Spirit in the synodal college that gives Tradition its binding force and allows it to be identified with faith and truth. The documentation of the African synods represents a decisive step in the evolution of the relationship between Rome and other bishoprics in terms of jurisdictional primacy or the authoritative role of Rome. In its ultimate repercussions, the issue is thus tinged with ecclesiological and ecumenical tones. The texts discussed here allow us to discover the enormous contribution of the African Church to the ancient Christian thought of this golden age, in which Fathers such as Aurelius, Alypius and Augustine himself were active.